The Fontan outcomes network: first steps towards building a lifespan registry for individuals with Fontan circulation in the United States. (8th August 2020) - Alsaied, Tarek; Allen, Kiona Y.; Anderson, Jeffrey B.; Anixt, Julia S.; Brown, David W.; Cetta, Frank; Cordina, Rachael; D'udekem, Yves; Didier, Meghan; Ginde, Salil; Di Maria, Michael V.; Eversole, Michelle; et al.
Abstract: The Fontan Outcomes Network was created to improve outcomes for children and adults with single ventricle CHD living with Fontan circulation. The network mission is to optimise longevity and quality of life by improving physical health, neurodevelopmental outcomes, resilience, and emotional health for these individuals and their families. This manuscript describes the systematic design of this new learning health network, including the initial steps in development of a national, lifespan registry, and pilot testing of data collection forms at 10 congenital heart centres.